Level of nickel in Scarus ghobban (parrotfish) caught in Manicani, Guiuan, Eastern Samar, Philippines - Opong, Jane Lovely A. (2016)
Mining poses serious threats to the environment as well as endangers the health of the inhabitants around it. Manicani Island has an open mining pit for saprolite which causes siltation and possible nickel contamination. Fishes are susceptible to heavy metal contamination and can pose health problems to the consumers, especially the commercially sold fishes. The parrotfish Scarus ghobban is one of the local commercially sold fishes. S. ghobban was digested using a tri-acid of sulfuric, perchloric and nitric acid then tested for nickel content using Atomic Absorption Spectrophotometer. The fish samples showed that they contain some amount of nickel which ranged from 2.07 to 2.99 mg/kg. The results exceeded the maximum acceptable limit of nickel for fish food set by the World Health Organization which is 0.5-0.6 mg/kg.